Modular nature of simian foamy virus genomes and their evolutionary history - Katzourakis, A; Aiewsakun, P; Richard, L; Gessain, A; Mouinga-Ondémé, A; Afonso, P (Oxford University Press, 2019)
Among all known retroviruses, foamy viruses (FVs) have the most stable virus–host co-speciation history, co-diverging in concert with their vertebrate hosts for hundreds of millions of years. However, detailed molecular analyses indicate that different parts of their genome might have different evolutionary histories. While their polymerase gene displays a robust and straightforward virus–host co-speciation pattern, the evolutionary history of their envelope (env) gene, is much more complicated. Here, we report eleven new FV env sequences in two mandrill populations in Central Africa, geographically separated by the Ogooué River into the North and the South populations. Phylogenetic reconstruction of the polymerase gene shows that the two virus populations are distinct, and each contains two variants of env genes co-existing with one another. The distinction between the two env variants can be mapped to the surface domain, flanked by two recombination hotspots, as previously reported for chimpanzee and gorilla FVs. Our analyses suggest that the two env variants originated during the diversification of Old World monkeys and apes, ∼30 million years ago. We also show that this env gene region forms two phylogenetically distinct clades, each displaying a host co-divergence and geographical separation pattern, while the rest of the genome of the two strains is phylogenetically indistinguishable in each of the host-specific groups. We propose possible evolutionary mechanisms to explain the modular nature of the FV genome.